Early chilhood parenting based on islamic value and local culture in strengthening family resilience and role - Septya Suarja; Husnani Aliah; Muhammad Irham Zainuri; Abdul Kadir; A. Nurhayati; Elhadfa Laabed (Jurnal Konseling dan Pendidikan, 2025)
The main challenge in early childhood parenting based on Islamic values ​​and local culture lies in the gap between the ideal principles taught in religious teachings and the culture influenced by modernization. This study aims to examine early childhood parenting patterns based on Islamic values ​​and local culture as an effort to strengthen the family's role in character formation of the children. Using a qualitative approach and phenomenological methods, this study involved five families selected through snowball sampling in Palopo City, South Sulawesi. Data were collected through observation, in-depth interviews, and documentation, then analysed using reduction techniques to uncover key themes from parenting experiences. The results show that parents implement various strategies in Islamic parenting, such as inviting children to worship, limiting interaction between boys and girls, developing Islamic character, and instilling values ​​of faith and honesty from an early age. Furthermore, the Bugis Makassar cultural approach is also an important part of parenting, instilling values ​​such as Alempureng (honesty), Amaccang (intellectualism), Agenttengeng (assertiveness), Reso (hard work), and Siri (shame/self-esteem). The integration of Islamic values ​​and local culture strengthens family resilience and shapes children's identities with noble character. These findings emphasize the importance of parents as the first educators in the family and the need for a holistic approach to early childhood parenting. This research contributes to the development of parenting models that align with Islamic teachings and local wisdom, and are relevant in the context of a multicultural society.